Bacterial infections in patients with acute variceal bleeding in the era of antibiotic prophylaxis - Martínez, Javier; Hernández-Gea, Virginia; Rodríguez-de-Santiago, Enrique; Téllez, Luis; Procopet, Bogdan; Giráldez, Álvaro; Amitrano, Lucio; Villanueva, Candid; Thabut, Dominique; Ibañez-Samaniego, Luis; Silva-Junior, Gilberto; Genescà, Joan; et al. (Journal of hepatology, 2021)
Antibiotic prophylaxis reduces the risk of infection and mortality in patients with cirrhosis and acute variceal bleeding (AVB). This study examines the incidence of, and risk factors for, bacterial infections during hospitalization in patients with AVB on antibiotic prophylaxis. A post hoc analysis was performed using the database of an international, multicenter, observational study designed to examine the role of pre-emptive transjugular intrahepatic portosystemic shunts in patients with cirrhosis and AVB. Data were collected on patients with cirrhosis hospitalized for AVB (n = 2,138) from a prospective cohort (October 2013-May 2015) at 34 referral centers, and a retrospective cohort (October 2011-September 2013) at 19 of these centers. The primary outcome was incidence of bacterial infection during hospitalization. A total of 1,656 patients out of 1,770 (93.6%) received antibiotic prophylaxis; third-generation cephalosporins (76.2%) and quinolones (19.0%) were used most frequently. Of the patients on antibiotic prophylaxis, 320 patients developed bacterial infection during hospitalization. Respiratory infection accounted for 43.6% of infections and for 49.7% of infected patients, and occurred early after admission (median 3 days, IQR 1-6). On multivariate analysis, respiratory infection was independently associated with Child-Pugh C (odds ratio [OR] 3.1; 95% CI 1.4-6.7), grade III-IV encephalopathy (OR 2.8; 95% CI 1.8-4.4), orotracheal intubation for endoscopy (OR 2.6; 95% CI 1.8-3.8), nasogastric tube placement (OR 1.7; 95% CI 1.2-2.4) or esophageal balloon tamponade (OR 2.4; 95% CI 1.2-4.9). Bacterial infections develop in almost one-fifth of patients with AVB despite antibiotic prophylaxis. Respiratory infection is the most frequent, is an early event after admission, and is associated with advanced liver failure, severe hepatic encephalopathy and use of nasogastric tube, orotracheal intubation for endoscopy or esophageal balloon tamponade. Bacterial infections develop during hospitalization in close to 20% of patients with acute variceal bleeding despite antibiotic prophylaxis. Respiratory bacterial infections are the most frequent and occur early after admission. Respiratory infection is associated with advanced liver disease, severe hepatic encephalopathy and a need for a nasogastric tube, orotracheal intubation for endoscopy or esophageal balloon tamponade. [Display omitted] •Bacterial infections still occur in around one-fifth of patients with cirrhosis and acute variceal bleeding despite antibiotic prophylaxis.•Respiratory bacterial infections are the most frequent, occurring early after admission.•Respiratory infections are related to the severity of cirrhosis, presence of severe hepatic encephalopathy and airway manipulation.•Over 50% of the bacteria isolated in this series were resistant to third-generation cephalosporines.